A live attenuated H5N2 prime- inactivated H5N1 boost vaccination induces influenza virus hemagglutinin stalk specific antibody responses. Issue 4 (22nd January 2020) - Kongchanagul, Alita; Samnuan, Karnyart; Wirachwong, Ponthip; Surichan, Somchaiya; Puthavathana, Pilaipan; Pitisuttithum, Punnee; Boonnak, Kobporn
Abstract: Background: The emergence and spread of highly pathogenic avian influenza (H5N1) viruses have raised global concerns of a possible human pandemic, spurring efforts towards H5N1 influenza vaccine development and improvements in vaccine administration methods. We previously showed that a prime-boost vaccination strategy induces robust and broadly cross-reactive antibody responses against the hemagglutinin globular head domain. Here, we specifically measure antibodies against the conserved hemagglutinin stem region in serum samples obtained from the prior study to determine whether stalk-reactive antibodies can also be induced by the prime-boost regimen. Method: Serum samples collected from 60 participants before vaccination and on days 7, 28 and 90 following boosting vaccination were used in this study. 40 participants received two doses of live attenuated H5N2 vaccine (LAIV H5N2) followed by one dose of inactivated H5N1 vaccine a year later, while 20 participants received only the inactivated H5N1 vaccine. We tested these serum samples for stalk-reactive antibodies via enzyme-linked immunosorbent (ELISA) and microneutralization assays. Results: Stalk-specific antibody levels measured by both assays were found to be significantly higher in primed individuals than the unprimed group. ELISA results showed that 22.5, 70.5 and 57.5% of primed participants had a four-fold or more increase in stalk antibody titers on days 7, 28 and 90 following boosting vaccination, respectively; whereas the unprimed group had no increase. Peak geometric mean titers (GMT) for stalk antibodies in the LAIV H5N2 experienced group (24, 675 [95% CI; 19, 531–31, 174]) were significantly higher than those who received only the inactivated H5N1 vaccine (8877 [7140–11, 035]; p < 0·0001). Moreover, stalk antibodies displaying neutralizing activity also increased in primed participants, but not in the unprimed group. Conclusion: Our finding emphasizes the importance of prime-boost vaccination for effectively inducing stalk antibodies, which is an attractive target for developing vaccines that induce stalk reactive antibodies.